A national study of clinical and laboratory factors affecting the survival of patients with multiple drug resistant tuberculosis in the UK. Issue 9 (1st September 2002) - Drobniewski, F; Eltringham, I; Graham, C; Magee, J G; Smith, E G; Watt, B
Abstract : Background: This study aimed to describe the clinical, microbiological, molecular epidemiology and treatment of multidrug resistant tuberculosis (MDRTB) cases in the UK and to determine factors associated with survival. Methods: Ninety MDRTB cases were identified from 1 January 1996 to 30 June 1997; 69 were DNA fingerprinted. Date of diagnosis was determined and data were collated on key demographic factors, clinical, radiological and treatment details. Variables associated with survival were included in a Cox proportional hazards model. Results: Most of the patients (72.4%) were male, born outside the UK (57.1%), were sputum smear positive (82.2%), and had entered the UK more than 5 years previously (61.9%). Thirty eight of 78 cases (48.7%) had prior TB. Sufficient data on 82 patients were available for survival analysis; 20/27 (74.1%) known to be dead at the end of the observation period had died of tuberculosis. Median survival time overall was 1379 days (95% CI 1336 to 2515) or 3.78 (95% CI 3.66 to 6.89) years (858 days (95% CI 530 to 2515) in immunocompromised individuals (n=32) and 1554 (95% CI 1336 to 2066) days in immunocompetent cases (n=48)). Median survival in patients treated with three drugs to which the bacterium was susceptible on in vitro testing (n=62) was 2066 days (95% CI 1336 to 2515) or 5.66 years, whereas in those not so treated (n=13) survival was 599 days (95% CI 190 to 969) or 1.64 years. Conclusions: Immunocompromised status, failure to culture the bacterium in 30 days or to apply appropriate three drug treatment, and age were significant factors in mortality. An immunocompromised patient was nearly nine times more likely to die, while application of appropriate treatment reduced the risk (risk ratio 0.06). Increasing age was associated with increasing risk of death (risk ratio 2.079; 95% CI 1.269 to 3.402)—that is, for every 10 year increase in age the risk almost doubled. Overall survival was lower than that reported in previous studies.